THE ROLE OF SOCIOCULTURAL THEORY IN THE LEARNING PROCESS AT ISLAMIC EDUCATIONAL INSTITUTIONS - Nuryadin, Riyan; Awaliyah, Siti Aini Latifah; Warto, Priawon Cendra; Mirwan4, Mirwan4; Ruswandi, Uus (FORUM PAEDAGOGIK, 2025)
The learning process in Islamic educational institutions faces many challenges. In the midst of the development of the times and social changes, Pesantren as a form of Islamic educational institution, is required to remain relevant in meeting the learning needs of students, without leaving the roots of strong Islamic traditions. Sociocultural theory can be the foundation for understanding and developing learning approaches that are in accordance with the characteristics of Islamic education today. This study aims to analyze the main concepts of sociocultural theory in Islamic education practice and examine the role of sociocultural theory in the learning process at the Islamic Union Islamic Boarding School No. 19 Bentar Garut. This research was carried out with a Case Study approach, with several stages, namely: Literature Review, Field Observation, In-depth Interview, and Data Analysis. The results of the study show that the main concepts of sociocultural theory in Islamic educational practice include the theory of Proximal Development Zones (PDZ), Mediated Learning, Community Roles, and Language and Culture as a tool for developing understanding. Sociocultural theory plays an important role in Islamic educational institutions, especially in the Persatuan Islam Islamic Boarding School No. 19 Bentar Garut, West Java. The key role of sociocultural theory in learning in Islamic boarding schools is illustrated in the process of social interaction, the use of cultural tools, the formation of identity through the community, Islamic education as a social process, and learning that is relevant to the real life of students in their daily lives.